Lesões não neoplásicas da glândula mamária de cadelas e sua relação com neoplasias adjacentes - Wilson, Tais Meziara (2017)
Few studies analyzing non-neoplastic lesions (NNL) in mammary gland of female dogs, as well as the relation between the presence of these alterations and the simultaneous occurrence of mammary neoplasias, either in the mammary tissue adjacent of mammary neoplasm or in the other breasts of the mammary chain with tumor. The objective of this study was to determine the occurrence of non-neoplastic lesions in the mammary tissue adjacent to tumors in breasts with no palpable nodules located in the mammary chains of female dogs with neoplasms and to correlate with histological type and grade of carcinoma. For this, a histological analysis of 314 breast samples with or without a palpable nodule of 68 bitches submitted to mastectomy was performed. The neoplastic and non neoplastic alterations located adjacent to the tumors and also in the breasts without palpable nodules in the mammary chain were identified. Their occurrence was associated with malignant neoplasms and benign by a contingency analysis (Fischer's exact test). The minimum age of bitches in this study (3 years) coincides with the occurrence of the first or second estrous cycle. In breasts with no palpable nodules associated with breast neoplasms there is an occurrence of NNL and neoplastic lesions, demonstrating the risk of developing a new mammary neoplasia in other glands of dogs diagnosed with breast carcinoma. This data reinforces the recommendation to perform total mastectomy, even in female dogs with only one node in the chain. NNL of the gland adjacent to neoplasias and in the other breasts without nodules were more frequently associated with malignant neoplasias when compared with benign neoplasias. Mammary glands without nodules in mammary chains with more than one type of malignant neoplasm had more NNL than those with only one type of neoplasia. ALH, which is considered the precursor of invasive breast carcinomas in bitches, occurred more frequently associated with carcinomas than other types of hyperplasia.